Smart guaranteed time‐slot allocation algorithm for industrial wireless sensor networks emergency message transmission. (1st April 2015) - Chen, Qinyin; Hu, Yanting; Chen, Zhe; Davies, John N.; Excell, Peter
Abstract : This paper presents investigation on application of wireless sensor networks (WSNs) in wind power generation systems and highlights an important issue associated with the deadline for the delivery of messages among nodes based on the IEEE 802.15.4E standard. Owing to the limits of standard and the power system application requirements, this research proposes a smart guaranteed time slot (S‐GTS) allocation algorithm which is based on the urgent/important matrix. This proposed algorithm promotes the utilisation of contention free period in a superframe. Besides, over seven GTSs can be allocated in a superframe, there are only seven GTSs that can be used in the standard. In addition, this study proves the value of BO and SO upper bound is 6 for the WSN application in power systems. Moreover, the network delay of S‐GTS performs better than the 16‐time‐slot mechanism and i‐GAME mechanism.